UKRAINIAN STUDIES COMPONENT IN THE WORKS OF AMERICAN WRITERS AS A SOURCE OF NATIONAL IDENTITY FORMATION IN CHILDREN AND YOUTH - Trukhan, Oksana (Mountain School of Ukrainian Carpaty, 2024)
The purpose of the article is to analyze the Ukrainian studies component in the literary works of selected American writers as a source for shaping the national identity of children and youth. Fiction possesses a significant educational potential. Contemporary world literature, encompassing literary works created from the 1990s to the present, is diverse in both content and form. A notable contribution is made by American authors of Ukrainian origin, including Yuriy Tarnawsky, Askold Melnyczuk, Irene Zabytko, Alexander Motyl, Anya Yurchyshyn, Marina Lewycka, Orest Pelekh, Olena Jennings, Dzvinia Orlovsky, and others. While their literary works are written in English, thematically, they are deeply connected with Ukraine, with Ukrainian studies prominently represented in their creative output. This layer of diaspora literature is virtually unknown to Ukrainian students and learners. Nonetheless, it serves as an effective medium for fostering spirituality, national-patriotic sentiments, and historical memory, addressing issues of national identity and the realization of one's national self, which are especially critical in the face of contemporary challenges, such as Russian aggression. This study examines the works of American writers of Ukrainian descent, including Irene Zabytko (notably «The Sky Unwashed», «When Luba Leaves Home», and the short story «Obligation»), Askold Melnyczuk («The House of Widows»). The analysis highlights literary depictions of historical memory, illustrating its connection to traumatic experiences of violence, loss of homeland, and emigration, with Zabytko presenting her narrative through a female perspective. These authors share a common heritage, having been born into families of Ukrainians who emigrated to the United States after World War II. This generation of emigrants is notable for its cultural assimilation, bearing dual identities, which necessitates great resilience to live with such duality.